1992
DOI: 10.1007/bf00374228
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of myocardial cross-bridge turnover rate in presence of EMD 53998, a novel Ca2+-sensitizing agent

Abstract: We have studied the effect of EMD 53998 (5-(1-(3,4-dimethoxybenzoyl)-1,2,3,4-tetrahydrochinolin-6-yl)-6-me thyl-3,6-dihydro-2H-1,3,4-thiadiazin-2-one) on cross-bridge turnover rate at varying Ca2+ concentrations. Cross-bridge cycling rate was estimated both by adenosine triphosphatase measurements and determination of mechanical characteristics of constantly activated fibres, which is assumed to reflect cross-bridge kinetics. The results indicate that the turnover rate of myocardial cross-bridges was reduced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 10 publications
4
9
0
Order By: Relevance
“…Myofilament Ca2+ sensitizers, including pimobendan (7,13,56), sulmazole (62), and EMD 53998 (6,11,29), augment Ca2+ binding to the Ca2'-specific regulatory site of cardiac troponin C, leading to prolonged systolic interaction of actin and myosin filaments (31). These agents also partially inhibit vascular smooth muscle and cardiac phosphodiesterases (PDEs) (7,12,35,59), resulting in systemic and pulmonary vasodilation, further augmentation of contractile function, and direct positive lusitropic (relaxation) effects (50).…”
Section: Introductionmentioning
confidence: 99%
“…Myofilament Ca2+ sensitizers, including pimobendan (7,13,56), sulmazole (62), and EMD 53998 (6,11,29), augment Ca2+ binding to the Ca2'-specific regulatory site of cardiac troponin C, leading to prolonged systolic interaction of actin and myosin filaments (31). These agents also partially inhibit vascular smooth muscle and cardiac phosphodiesterases (PDEs) (7,12,35,59), resulting in systemic and pulmonary vasodilation, further augmentation of contractile function, and direct positive lusitropic (relaxation) effects (50).…”
Section: Introductionmentioning
confidence: 99%
“…Prolongation of relaxation time was even more pronounced in hypoxic myocytes, possibly as a direct consequence of increased cytoplasmic calcium loading under these conditions (127). The absence of contractile economy in intact heart preparations contrasts with data using cardiac muscle strips, were economization of contraction cost was reported with both the racemic mixture (44,65,106) and the calcium-sensitizing (+)-isomer (34,77). The reason for this discrepancy remains unclear.…”
Section: Emds 7033mentioning
confidence: 87%
“…In general, EMD 53998 enhanced maximal ATPase activity (89). In apparent contrast, this racemate reduced ATPase activity in skinned porcine cardiac fibers, but this effect was seen only at low Ca2+ concentrations (61). Other studies showed that the (+)-enantiomer of EMD 53998 (EMD 57033) stimulated the actomyosin ATPase in cardiac myofibrils (27,87) and in a concentration-dependent manner in skinned fibers (63).…”
Section: Effects On Myofibrillar Atpase Activitymentioning
confidence: 94%
“…In skinned myocardial fibers, EMD 53998 reduced tension cost at low Ca2+ concentrations (pCa 2 6.25) but not at higher concentrations (pCa =s 5.85) (61). On the other hand, the drug was reported to increase energy efficiency of intact papillary muscles (59).…”
Section: Effects Otz Energetics and Eficiencymentioning
confidence: 98%
See 1 more Smart Citation